2018
DOI: 10.3389/fpsyg.2018.00695
|View full text |Cite
|
Sign up to set email alerts
|

Machiavellian Ways to Academic Cheating: A Mediational and Interactional Model

Abstract: Academic cheating has become a pervasive practice from primary schools to university. This study aims at investigating this phenomenon through a nomological network which integrates different theoretical frameworks and models, such as trait and social-cognitive theories and models regarding the approaches to learning and contextual/normative environment. Results on a sample of more than 200 Italian university students show that the Amoral Manipulation facet of Machiavellianism, Academic Moral Disengagement, De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
40
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 110 publications
2
40
0
4
Order By: Relevance
“…Since then, academic cheating has been a problem and continues to concern the educational communities. Studies have shown that academic cheating has become increasingly prevalent (Antneh and Asres 2014; Barabanell et al 2018;Dyer et al 2020;Jennifer et al, 2009 andMebratu 2016) and is becoming a habit for a growing number of students (Bacon et al 2019;Löfström and Kupila 2013;Miller et al 2015;Quaraishi and Aziz 2017;Rana and Ajmal 2013;Davis et al 2009;and Thomas et al, 2010). In the past 50 years, the number of students that self-report consistent or frequent cheating increased rather sharply, especially in regard to cheating on tests (Bertram Gallant 2020;McCabe et al 2012;Parnther 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Since then, academic cheating has been a problem and continues to concern the educational communities. Studies have shown that academic cheating has become increasingly prevalent (Antneh and Asres 2014; Barabanell et al 2018;Dyer et al 2020;Jennifer et al, 2009 andMebratu 2016) and is becoming a habit for a growing number of students (Bacon et al 2019;Löfström and Kupila 2013;Miller et al 2015;Quaraishi and Aziz 2017;Rana and Ajmal 2013;Davis et al 2009;and Thomas et al, 2010). In the past 50 years, the number of students that self-report consistent or frequent cheating increased rather sharply, especially in regard to cheating on tests (Bertram Gallant 2020;McCabe et al 2012;Parnther 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, both students and lecturers believe that it is easier to cheat in online courses (Kennedy et al, 2000 ). This is a worrysome phenomenon since cheating has consequences both for the students' learning process in the course of their academic studies and for the employment market that will receive them following their graduation, with the ethics they bring to that market (Barbaranelli et al, 2018 ; Bashir & Bala, 2018 ). Exams and assignments are now all conducted online and it appears that they will be conducted thus at least in the forseeable future.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the main purpose of teaching and learning as perceived today is to foster a learning-oriented environment, based on personal motivation, more than creating an achievement-directed environment (Bertram Gallant, 2017 ). And indeed, when the student learns through intrinsic motivation, academic practices are usually fair (Barbaranelli et al, 2018 ; Krou et al, 2020 ). These values, which underlie academic integrity, are considered important even in times of duress, which may stem from lack of knowledge and fear of failure (Keohane, 1999 ), or from crises such as the present pandemic (Moralista & Oducado, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations